Design of Development Waste Heat Recovery in Metal Casting Industry: Exploring Energy Saving Potentials - Saiful, Rifki; Hilmi, Erik; Nasrullah, Nasrullah; Uhanto, Uhanto; Arneta, Vanesa; Rifiana Dewi, Shanaya (Program Studi Magister Energi, Sekolah Pascasarjana, Universitas Diponegoro, Indonesia, 2025)
The metal casting industry is known for its energy-intensive consumption and the generation of large amounts of waste heat and materials during the melting, casting, and cooling processes. If this heat is not utilized properly, it not only causes environmental degradation but also contributes to significant economic inefficiencies. Therefore, the need for more sustainable practices is increasingly driving the industry to seek solutions to optimize energy consumption and reduce waste. One promising solution is the implementation of waste heat recovery (WHR) systems, which aim to model waste heat recovery, evaluate potential energy savings, and provide solutions to improve sustainability in the sector. By developing hybrid system designs that combine fossil fuels and renewable energy sources, such as solar panels (PV), batteries, and inverters, the industry can reduce its reliance on fossil fuels while improving overall energy efficiency. Furthermore, the implementation of WHR technology not only offers technical benefits but also contributes to lower operational expenses and carbon emissions, as demonstrated by the reduction in unit production costs from various simulations. These results demonstrate that this new system has positive economic and environmental impacts, creating a more environmentally friendly and sustainable solution for the metal casting industry.